Association of pneumonia with mortality of burn patients in the burn unit: A retrospective cohort study - I Gusti Putu Hendra Sanjaya; Agus Roy Rusly Hariantana Hamid; Tjokorda Gde Agung Senapathi; Anak Agung Ayu Anggreni; Anak Agung Gde Putra Semara Jaya (Bali Journal of Anesthesiology)
Abstract Background: Burn injuries are catastrophic. Infection remains a significant risk after burns. Pneumonia occurring during hospitalization requires particular care as it is induced by infectious agents within the healthcare facility, significantly distinct from those that cause pneumonia in the community. The incidence of pneumonia will increase in patients with severe burns. This study investigates the association between pneumonia and mortality of burn patients in the burn unit. Subjects and Methods: This observational study utilized a retrospective cohort design, analyzing secondary data from patients’ medical records. A total of 78 eligible research subjects were consecutively selected from burn patients treated at the Burn Unit of Ngoerah Hospital from January 2020 to December 2022. Patient characteristics, burn profiles, mortality, confounders, and other related data were recorded and analyzed. Results: Among the 78 subjects, 61 (78.21%) were categorized as having severe burn injuries, 42 (53.85%) had pneumonia, and 30 (38.5%) died during hospitalization. Among the deceased, 20 subjects (73.3%) were burn patients with pneumonia. Death was more frequent in burn patients with pneumonia (52.4% (22/42)) compared to those without pneumonia (22.2% (8/36)). Using logistic regression multivariate analysis, we found greater odds of association between pneumonia and mortality with the adjusted odds ratio of 1.18 (95% CI 0.35–4), controlling for variables such as inhalation injury, total body surface area, depth of burn, and burn etiology. Conclusions: Pneumonia is potentially associated with higher odds of mortality compared to non-pneumonia in burn patients.